Electrochemical Studies of Nano Metal Oxide Reinforced Nickel Hydroxide Materials for Energy Storage Applications. (2017) - Ravikumar, C.R.; Kotteeswaran, P.; Murugan, A.; Bheema Raju, V.; Santosh, M.S.; Nagaswarupa, H.P.; Nagabhushana, H.; Prashantha, S.C.; Anil Kumar, M.R.; Gurushantha, K.
Abstract: The electrode materials for secondary battery and supercapacitor applications have been synthesized by co-precipitation of nickel hydroxide in NiSO4 aqueous solution and subsequently reinforced with MgO, ZnO, TiO2 and CuO nanoparticles (NPs). These nickel hydroxide materials exhibit a typical β-phase when characterized by powder X-ray diffraction (PXRD). Further, addition of nanoparticles additives have shown a variation in the band gap of nickel hydroxide as noticed from diffuse reflectance spectral (DRS) analysis. The electrochemical characteristics have been investigated by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). The CV measurements indicate an increase in the reversibility of the electrode reaction whereas by reducing the EO -ER value, nano metal oxide reinforced β-Ni(OH)2 exhibits an improved capacitance by increasing the conductivity of an electrode as evident from EIS measurements. Galvanostatic charge-discharge tests for the β-Ni(OH)2 samples with nano metal oxide additives have shown excellent capacitance performance in battery and supercapacitor applications. These results may offer new pathways for the development of novel materials for energy storage applications in general and contribute to the development of this niche area at large.